Biopori Sebagai Resapan Air dan Bank Pupuk Kompos di SDN. 067774 dan SDN. 067775, Kecamatan Medan Johor, Medan, Sumatera Utara - Sari, Suci Perwita; Amelia, Chairunnisa; Pratiwi, Indah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
Biopore holes are simple technologies for conservation and the provision of clean water made by punching holes in the ground and planting pipes inside. This technology can be applied in residential or school buildings that are 100% waterproof or there is no open land or in paddy fields located in hill that are very prone to flooding. This biopore can be used as a water catchment place to minimize the occurrence of puddles. This biopore also triggers the growth of organisms in the soil such as ants, worms and air so that it can fertilize the soil. Based on the implementation of the realization of biopore infiltration holes, an increase in the understanding of teachers and students towards the realization of biopore infiltration holes. The increasing in teachers at SDN. 067774 which at 55.75 to 92.83, an increase of 37.08. The teacher’s comprehension at SDN.067775 which was 57.42 to 92.25. This means an increase of 34,83. Students at SDN.067774 which at first 31.75 to 85.12. This means an increase of 53.37. Students at SDN.067775 which at first 28.14 occurred 82.83. An increase of 54.68. Realization of making biopori at SDN. 067774 and SDN.067775 were declared successful because they motivated teachers, principals and even students to be more concerned and aware to preserve the environment were easy. They are enthusiastic, this can be seen with students who throw leaf waste into the biopore and socialize the use of biopore. it is expected to be able to support schools to become adiwiyata schools